Gangs in America's communities - Howell, James C. 19XX- (SAGE, 2019)
Preface -- Acknowledgments -- About the authors -- History of gangs in the united states -- Myths and realities of youth gangs -- Defining gangs and gang members -- General macro-level theories and modern-day applications -- Micro-level theories : developmental life course pathways and other micro-level explanations for gang involvement -- Girls and gangs -- National gang problem trends : 1996 to 2012 -- Urban gangs and violence -- What works : prevention -- What works : intervention and suppression -- Glossary -- References -- Index